Anthropocentrism as the Semantic Basis of Phraseological Units (Based on English Idioms) - E.E. Vedmanova; N.V. Kulikova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The aim of the paper is to prove that English idioms are anthropocentric in their semantics. In order to achieve this aim, the method of continuous sampling from various lexicographic sources has been used to compile a representative corpus of 1200 English idioms. The idioms have been analyzed from the perspective of cognitive linguistics and linguistic modelling. As a result of the research, it has been found that the anthropocentric nature of English idioms is directly reflected in their themes: the vast majority of English idioms are associated with humans and everything they deal with – artefacts, appearance, character, life situations, human-made artefacts, etc.; only a few idioms are associated with natural objects and phenomena. Furthermore, the percentage of anthropocentric and other idioms that are not anthropocentric in their nature has been determined. The planes of content (theme, object of modelling) and expression (image) of idioms have been analyzed. Data obtained in this way have proved the assumption about the anthropocentric nature of English idioms. The results of the research are largely applicable in English phraseological theory, as well as in comparative phraseology.